FIRE -BASED MONITORING SYSTEM USING COMPUTER PERIPHERAL INTERFACE PRGRAMMABLE 8255 - Erwin Kurniawan; Fivtatianti Hendajani, SKom, MM (Jurnal Sistem Komputer, 2002)
In this tool the smoke sensor (LDR) is used to detect the situation room in case of fires. The sensor will be activated when there is smoke blocking light that illuminates the sensor, so mengasilkan data later via the data interface are processed by computer to activate the sirens and the simulation of an automatic sprinkler use and viewing of LED and relay room on the monitor screen to monitor the room where the fire occurred . That kind of thing is done continuously with the help of theÂ  direct control program displays the room where the fire occurred.Â